The Impact of Remittances on Domestic Investment in Developing Countries: Fresh Evidence From the Asia-pacific Region - Tung, Le Thanh (Organizations and Markets in Emerging Economies, 2018)
Despite the sharply increasing remittances in developing countries (especially in the AsiaPacific region), the relationship between remittances and domestic investment in recipient countries has not been fluently evidenced. This paper aims to fill the empirical gap in the Asia-Pacific region by investigating the impact of remittances on domestic investment with a sample including nineteen developing countries based on time series data from 1980 to 2015. However, our findings contradict some evidence from other regions. The results robustly confirm that remittances have a negative impact on domestic investment in these countries. Our results also indicate that the annual GDP per capita growth, official development assistance, domestic credit, gross saving, and inflation have a positive impact on domestic investment, however, we conclude that the impact of trade openness on domestic investment has a negative sign in the study period. The paper also provides some policy suggestions with regard to remittance flows in this region.
Keywords: remittances; domestic investment; GDP per capita growth; official development assistance; domestic credit; gross saving; inflation; Asia-Pacific region; developing countries